Gender, eating disorders, and graphic medicine - Peter, Anu; Venkatesan, Sathyaraj (New York : Routledge, 2020)
"Gender, Eating Disorders, and Graphic Medicine leaps past the prevalent notions on eating disorder, and contributes to the developing corpus of affective knowledge on eating disorders among women through comics and graphic medicine"--
OCLC-licensed vendor bibliographic record.
Keywords: Eating disorders in women; Medicine -- Comic books, strips, etc; PSYCHOLOGY / Psychopathology / Eating Disorders; SOCIAL SCIENCE / Gender Studies